Leveraging AI and Machine Learning to Detect and Prevent Cyber Security Threats - Hasnain Hussain; Maria Kainat; Mahpara; Taib Ali, (Dialogue Social Science Review (DSSR), 2025)
Cyber security threats continue to evolve in complexity, posing significant challenges to organizations and individuals worldwide. Leveraging artificial intelligence (AI) and machine learning (ML) has emerged as a transformative approach to detecting and preventing these threats in real time. This study explores the application of AI and ML in cybersecurity by analyzing their impact on threat detection accuracy, response time, and prevention success rates. Through a systematic evaluation of AI-driven threat detection systems, we found that ML algorithms increased detection accuracy to 95.7% compared to traditional rule-based systems, which achieved only 78.4%. Additionally, AI-powered anomaly detection reduced average response times from 45 minutes to 12 minutes, enabling faster mitigation of active cyber threats. Predictive ML models demonstrated the ability to identify 92% of potential zero-day vulnerabilities, significantly enhancing proactive defense capabilities. The study also highlights the scalability of AI-driven cyber security frameworks, capable of processing over 10 million events per second with a false positive rate of just 0.4%. Implementing these systems resulted in a 38% reduction in financial losses from cyber attacks in organizations adopting AI and ML solutions over a one-year period. Despite these advancements, challenges such as algorithm bias, adversarial attacks on ML models and data privacy concerns remain. The findings underscore the need for continuous innovation and ethical considerations in developing AI and ML solutions for cyber security. This research provides a quantitative foundation for organizations to adopt AI-driven tools, demonstrating their effectiveness in fortifying defenses against the ever-growing landscape of cyber security threats.